Optimization of treatment and diagnosis tactics at varicoseveins of lower extremities in military personnelin Mongolia - B. Tsedendoo (Бюллетень сибирской медицины)
In this study, we have examined 166 patients after surgical treatment as a part of combined treatment of varicose veins of lower extremities. Depending on the level of veno-venous shunt, the following clinical forms of varicosity were revealed: varicosity with predominance of high venovenous shunt, descending form with predominance of low veno-venous shunt, ascending form. Thus, chronic venous hypertension starts a chain of pathological reactions causing chronic changes in skin of lower extremities in Mongolian military personnel.